Pengaruh Kepatuhan Pola Makan dan Aktivitas Fisik Terhadap Kadar Gula Darah pada Pasien Diabetes Melitus di Puskesmas Kecamatan Cipayung Jakarta Tahun 2022 - Dyah Ayu Lestari; Achmad Nusantara (Universitas Malahayati Lampung, 2022)
ABSTRACTFlow of globalization in all fields has increased and brought changes to people's behavior and lifestyle, including family food consumption patterns, such as unhealthy lifestyle, high consumption of junk-food and fast food, consumption of high-calorie foods, consumption of fatty foods, consumption of cigarettes and alcohol, and low consumption of fiber, fruit and vegetables, and physical activity. These changes have unwittingly influenced the epidemiological transition with increasing cases of non-communicable diseases (NCDs) such as heart disease, tumors, diabetes, hypertension, kidney failure and so on (Sam et al, 2017). One of the non-communicable diseases (PTM) that has received a lot of attention is Diabetes Mellitus (DM). Based on data at the Ciapayung District Health Center, Jakarta in 2019-2021, Diabetes Mellitus patients have increased every year. Based on this, the researchers were interested in conducting a study entitled